CURRENT COMPUTER TECHNOLOGIES IN THE DIAGNOSIS OF TRACHEOMALACIA IN PATIENTS WITH CICATRICIAL TRACHEAL STENOSIS IN THE PERIOPERATIVE PERIOD - I. M. Koroleva; M. A. Mishchenko (Вестник рентгенологии и радиологии)
Objective: to analyze current radiodiagnostic techniques in identifying tracheomalacia (TM) and estimating its severity and extent in patients with cicatricial tracheal stenosis (CTS) and to determine the important characteristics of TM according to follow-up multislice computed tomography (MSCT) and magnetic resonance imaging (MRI) findings.Material and methods. The investigation included the results of examining 94 patients, 81 of whom were diagnosed with CTS. To analyze the efficiency of the studies, the patients were divided into three groups; a control group of patients was formed. The diagnosis of TM was verified by clinical examination, instrumental diagnosis, MSCT and MRI studies, and intraoperative revision. The patients’ postoperative features were taken into consideration. Diagnostic performance measures, such as sensitivity, specificity, and accuracy, were calculated. Static radiation techniques (MSCT and MRI) and follow-up procedures (fMSCT and fMRI) were compared.Results. The follow-up procedures were proven to be twice as informative for the detection of the symptoms of TM as the endoscopic method that is considered the main method for the diagnosis of pathological tracheal changes. The diagnostic capabilities of MSCT, fMSCT, MRI, and fMRI were determined; criteria for identifying TM were formulated. The use of the follow-up procedures to identify clinically significant TM in patients with CTS could radically alter surgical tactic in 36.9% of cases.Conclusion. The proposed algorithm for examination of patients with CTS, which includes follow-up radiation procedures to evaluate the functional state of the tracheal wall, makes it possible to determine an optimal treatment policy and to significantly reduce the risks of complications and disease recurrences.